The Habit of Singing the National Anthem in the Upper Grades at SDN 104, Bengkulu City (A Case Study on Teacher Knowledge) - Silvania, Novia; Parmadi, Bambang; Anggraini, Dwi (Jurnal Pembelajaran dan Pengajaran Pendidikan Dasar, 2025)
This research aims to describe the knowledge of the national compulsory song of high class teachers and the habit of singing the national compulsory song in the high class of SDN 104 Bengkulu City. This type of research is qualitative research with a case study approach. The subject of this research is a high class teacher. The instrument for this research is the researcher himself using observation sheets, interview sheets and documentation. The data analysis technique uses the Miles, Huberman and Saldana interactive model which consists of data collection, data condensation, data presentation and drawing conclusions. Data validity techniques through technical triangulation and member checking. The research results show that overall, the knowledge of high class teachers is quite good where the teachers are able to answer the 6 aspects assessed by researchers through the 3 national mandatory songs. Especially in terms of the meaning of the national mandatory song, the message contained in the song, and its implementation in students' daily lives. However, the teacher has not been able to answer questions regarding the names of figures or composers of national obligatory songs. As for getting used to singing the national obligatory song, this program has not run optimally. Where the habit should be carried out every day, but currently the habit of singing mandatory songs is only done when there is material related to national mandatory songs or singing activities such as PPKn and SBdP. Apart from that, in practice the teacher does not strengthen the students' character by conveying the meaning contained in the national obligatory song and only invites them to sing the obligatory song. This causes students' awareness of the importance of singing the national obligatory song to be lacking.